Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T16:34:23+02:00
Graniastosłup I
Pp = 8²√3/4 × 2
Pp = 64√3/2
Pp = 32√3

Pb = 3 × 8 × 6
Pb = 144

Pc = Pp + Pb
Pc = 32√3 + 144

Graniastosłup II
Pp = 2 × 6 × 4²√3/4
Pp = 12 × 16√3/4
Pp = 12 × 4√3
Pp = 48√3

Pb = 6 × 6 × 4
Pb = 144

Pc = 144 + 48√3

Graniastosłup III
Pp = 2 x 5 x 5
Pp = 50

Pb = 4 x 5 x 7
Pb = 140

Pc = 50 + 140
Pc = 190
1 5 1
2010-04-13T16:39:05+02:00
1)
Pp = 8²√3/4 × 2 Pb = 3 × 8 × 6
Pb = 144 Pp = 32√3


Pb = 3 × 8 × 6 Pc = Pp + Pb
Pb = 144 Pc = 32√3 + 144


2)
Pp = 2 × 6 × 4²√3/4 Pb = 6 × 6 × 4 Pc = 144 + 48√3
Pp = 12 × 16√3/4 Pb = 144
Pp = 12 × 4√3
Pp = 48√3

3)
Pp = 2 x 5 x 5 Pb = 4 x 5 x 7
Pp = 50 Pb = 140

Pc = 50 + 140
Pc = 190
1 5 1